Control of two Electrical Plants. Issue 4 (15th September 2017) - Rubio, José de Jesús; Lopez, Jesus; Pacheco, Jaime; Encinas, Rodrigo
Abstract: In this paper, a controller is recommended for the regulation of two electrical plants. Since electrical plants generate electricity all the time, the regulation to get that all the plant states reach constant behaviors is important. Two main characteristics of the introduced method are: (i) it is based in the separation of the plant model equations, only some model equations are chosen for the regulation while the other model equations are ignored, it avoids the difficulty in the consideration of the full plant model; (ii) the Lyapunov strategy is employed to analyze the stability of the selected model equations in the electrical plant, it lets to ensure the regulation purpose. The advised method is applied in a gas turbine and a wind turbine for the electricity generation.